Vitrectomy – absolute indication in case of intraocular foreign body localized in vitreous cavity or within vitreo-retinal interface - Robaszkiewicz, Jacek; Nowosielska, Agnieszka; Wójcik, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Ocular trauma is the leading cause of visual loss in young adults. Open globe injuries with intraocular foreign bodies are an important part of this group, and in general an early surgery is required, in order to preserve the visual acuity and the eye globe. Primary surgical repair and foreign body removal may be performed using external magnet or vitrectomy. Based on published reports and our clinical experience we think that vitrectomy is safer procedure, giving better chance for good postoperative visual outcome.